A quantitative correlation between polyethylene/graphene interfacial viscoelastic dissipation and deformation parameters: A molecular simulation study. (August 2018) - Javan Nikkhah, Sousa; Moghbeli, Mohammad Reza; Hashemianzadeh, Seyed Majid
Abstract: In this study, the influence of applied tensile stretching rate and temperature on amorphous polyethylene/graphene (PE/G) and polyethylene/amino functionalized graphene (PE/aFG) interfaces were studied via molecular dynamics (MD) simulations. The simulations results indicated that the interfacial adhesion during stretching process was increased with increasing the stretching rate (V) while decreased with increasing the temperature (T). This behavior can be connected to changing the polymer chains friction arisen from inadequate reorientation time, which especially happened at the higher stretching rates and lower temperatures. Furthermore, the amino functionalization of G strengthened both the thermodynamic work of adhesion and interfacial viscoelastic energy dissipation function, φ (V, T), in the interface deformation process. In fact, relying the chains on aFG surface with stronger interfacial interactions also increased the required energy for the chains to disentangle and reorient on the surface. Moreover, the stretching rate dependency of the φ value well follows a power law at all the stretching temperatures. The effect of stretching rate and temperature on φ value was simultaneously investigated utilizing the time-temperature superposition principle. Master curves of the simulation data, φ ( a T V), was obtained for PE/G and PE/aFG interfaces on which the horizontal ( a T ) and vertical shift factor ( b T ) were calculated using Williams-Landel-Ferry (WLF) equation and Bueche-Rouse theory, respectively.